Stres No More: Strategi Efektif Mengelola Stres di Tengah Kehidupan Digital - Hendrikson Febri (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
In today's fast-paced and always-connected digital life, many individuals experience increased stress due to various reasons. Major issues in the digital era include constant connectivity, information overload, social media pressure, distractions and multitasking, work-life balance, social isolation, and mental and physical health concerns. The aim of this research is to explore how to manage stress effectively to achieve a state of "stress no more" amidst the digital landscape. This study employs a qualitative research approach. The findings suggest strategies for managing stress, such as limiting gadget use, implementing digital detox, maintaining life balance, managing information wisely, practicing relaxation techniques, and seeking help from psychological professionals and counselors.